Markets & institutions in real estate & construction - Ball, Michael, 1948- (Oxford ; Malden, MA : Blackwell Pub., 2006)
The book explains why the real estate and construction industries are organised in the ways they are and then relates those characteristics to long-term market behaviour. It covers market dynamics - supply and demand; the interaction of property development and construction - and examines institutions and market structures.
Prologue -- An introduction to the analysis of markets and institutions in real estate and construction -- House price cycles : evidence from recent European experience -- Improving housing markets -- Restructuring housing provision in Central and Eastern Europe -- International comparisons of estate agency/real estate brokerage services -- Spatial reach in commercial and residential real estate brokerage -- Financial services, mortgage markets, and real estate brokerage : an international survey -- International differences in the housebuilding industry -- The influence of size economies and planning regulations on the housebuilding industry -- Construction and real estate professions and practices -- The distinctiveness of large construction firms -- Multi-agent governance in property-led urban regeneration.
Includes bibliographical references (pages 250-263) and index.
Print version record.
English.
John Wiley and Sons
Keywords: Real estate business; Real estate business -- Europe; Construction industry; Immobilier; Immobilier -- Europe; Construction -- Industrie; BUSINESS & ECONOMICS -- Real Estate -- General; Construction industry; Real estate business; Europe; Onroerend-goedmarkt.; Bouwnijverheid; Europa (geografie)